Single-sided magnetic nanoparticles imaging scanner for early detection of breast cancer - Abubakar Sadiq, Abdulkadir (2018)
Electromagnetic coils form the basis of magnetic particle imaging (MPI) scanners. Previous scanner designs employ Helmholtz coil arrangement which has low sensitivity and high cost of fabrication. Furthermore, the scanners have long signal acquisition time and high memory requirement. This research focuses on developing a simple, low-cost and low memory demanding one-dimensional MPI scanner capable of imaging the position and concentration of magnetic nanoparticles (MNPs), using electromagnetic coils in the form of solenoids. The scanner produces an oscillatory magnetic field to excite the MNPs and a static magnetic field to confine the region of interest. The MNPs reacted with a nonlinear magnetisation response, inducing a voltage signal that was measured with an appropriate gradiometer pickup coil. In Fourier space, the received voltage signal consists of the fundamental excitation frequency and harmonics. This research utilises the second harmonic response of the MNPs to determine their position and concentration. Analogue Bandpass and Bandstop filters were designed for signal excitation and reception. Resovist and Perimag MNPs in liquid and immobilised form were used as tracer materials, which were moved to different spatial positions through the field of view (FOV), to record the induced voltages. The magnitude response of the Bandpass filter with 22.8 kHz fundamental frequency shows a flat amplitude in the passband with a smooth roll-off rate of ±80 dB/pole, while the Bandstop filter efficiently attenuates the fundamental frequency and passed the 45.6 kHz second harmonic frequency. Results of the excitation coil design revealed that a magnetic field within the range of 0.8 mT to 4.4 mT was obtained, while a voltage in microvolts range was induced in the gradiometer pickup coil. The contour maps derived from imaging one and two samples of the MNPs in the XY-plane revealed their position and shape. Additionally, the average threshold of the peak signal amplitude was obtained as 10.63 μV that would indicate the presence of MNPs concentration sufficient for cancer detection. The developed single-sided MPI scanner has a spatial resolution of less than 1 mm, a pixel resolution of 51.5 megapixels and 42.1 ms image acquisition time. Thus, the outcome of this research showed that the developed single-side MPI scanner has a potential in the detection of MNPs, which could help in sentinel lymph node biopsy for breast cancer diagnosis.